Minat beli konsumen Nobby Hijab Salatiga: Pengaruh eWOM, influencer marketing, dan Islamic brand congruence melalui citra merek - Putri, Megawati Guntari; Rofiuddin, Mohammad (Nur Science Institute, 2023)
This article aimed to determine the effect of electronic word of mouth (eWOM), influencer marketing, and Islamic brand congruence on purchase intention with brand image as a mediating variable. This type of research is quantitative, with a population of Nobby Salatiga consumers. The sampling technique in this study used purposive sampling with 100 respondents. The analysis technique used is path analysis. Statistical test results show that eWOM has an effect, while influencer marketing and Islamic brand Congruence do not affect productivity. eWOM, influencer marketing, and Islamic brand congruence affect brand image. Brand image as a mediating variable cannot mediate eWOM on purchase intention but can mediate Influencer Marketing and Islamic Brand Congruence on purchase intention.